PEF hydrogen bond reinforced modified polyester material and preparation method thereof
By introducing a third monomer hydroxy acid into PEF, a copolyester material with hydrogen bond reinforcement is solved, and the problem of taking into account the toughness and barrier properties of PEF modified polyester materials is achieved, and performance improvement and application expansion is achieved.
Patent Information
- Application Number
- CN202510188353.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult for existing PEF modified polyester materials to take into account both toughness and barrier properties.
By blending 2,5-furandicarboxylic acid with the third monomer hydroxy acid and copolymerizing under the action of ethylene glycol, a PEF hydrogen bond reinforcement is formed to enhance its toughness and barrier properties.
It is achieved to improve the toughness, melt strength and crystallization rate of PEF without destroying the regularity of PEF chain, while maintaining or improving its barrier properties.
Smart Images

Figure CN119875090A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PEF modified copolyester materials, in particular to a PEF hydrogen bond enhanced modified polyester material and a preparation method thereof. Background Art
[0002] Polyesters derived from 2,5-furandicarboxylic acid (FDCA), including PEF and poly(propylene 2,5-furandicarboxylate) (PPF), generally have higher glass transition temperatures (T g ). In addition, PEF has superior stiffness, strength and higher gas barrier properties than PET, and its O2 and CO2 permeability are 5-11 times and 2-19 times lower than PET, respectively. In addition, compared with PET, it is expected that greenhouse gas emissions from PEF production will be reduced by 45-55% and non-renewable energy use will be reduced by about 40-50%. Due to its excellent sustainability and superior thermomechanical and gas barrier properties, PEF is an excellent alternative to PET in the future, with great application potential and market prospects.
[0003] Due to the rigidity of the PEF skeleton, it has low crystallinity and slow crystallization rate, making it difficult to induce crystallization by stretching and difficult to process. In addition, there are problems such as brittleness, strong rigidity and insufficient toughness, which must be overcome before its successful industrial application. PEF can be modified by copolymerization or even by biaxial stretching orientation. Block or random copolymerization is also an effective way to improve the toughness of PEF: poly (ethylene glycol-co-1,4-cyclohexyl-2,,5-furan dicarboxylate) (PECF) containing 32-76 mol% of 1,4-cyclohexyl-2,,5-furan dicarboxylate units increases the elongation at break (50-186%) and maintains a fairly good tensile strength (71-59 MPa) and modulus (2.2-1.7 GPa), but due to the destruction of the regularity of the PEF polyester chain, the interaction strength between the chains of the PEF copolyester and the chain stacking density are reduced, and the gas barrier property is reduced.
[0004] Therefore, how to improve the toughness of PEF while maintaining or even further improving the excellent barrier properties of PEF is of great significance to the development of the performance of PEF polyester materials and the expansion of their applications. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a PEF hydrogen bond enhanced modified polyester material and a preparation method thereof, so as to solve the problem that the existing PEF modified polyester material cannot take into account both toughness and barrier properties.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, wherein 2,5-furandicarboxylic acid is blended with a third monomer hydroxy acid, and then copolymerized under the action of ethylene glycol to form a bio-based furan polyester, namely, a PEF hydrogen bond enhanced modified polyester material.
[0007] In the above technical scheme of the present invention, a PEF copolyester material is provided that enhances toughness, melt strength and barrier properties by copolymerization of a third monomer. The technical concept of the present invention is to introduce a hydroxyl group to form a third monomer with 2,5-furandicarboxylic acid (FDCA) as the core or to use the amide of the furan ring as the third monomer, and to modify the PEF chain without destroying the regularity of the PEF chain. The third monomer hydroxy acid is copolymerized with FDCA and ethylene glycol (EG) to synthesize a bio-based furan polyester, thereby introducing additional hydrogen bonds in PEF, and improving the performance of PEF by hydrogen bonding. By designing and synthesizing the third monomer structure and hydrogen bond form, a third monomer structure that does not destroy the regularity of the PEF chain and meets the requirements of food safety applications is obtained. After addition, the crystallization rate of PEF and the packing density between PEF chains can be increased, thereby improving the performance of PEF and enhancing its toughness and crystallization rate. The present invention explores the influence and application of hydrogen bonds on the barrier properties of polyester materials, which can guide the subsequent PEF modification direction and the development of high-performance materials to achieve sustainable development.
[0008] Preferably, the third monomeric hydroxy acid is selected from one or more of 5-hydroxyisophthalic acid (5-HIPA), 2,5-hydroxyterephthalic acid, 5-hydroxyisophthalic acid dimethyl ester, 5-carboxyvanillic acid, 4,5-dihydroxyisophthalic acid and 4,5,6-trihydroxyisophthalic acid.
[0009] Preferably, the molar ratio of the 2,5-furandicarboxylic acid to the third monomeric hydroxy acid is (90-99.5):(0.5-10).
[0010] Preferably, the molar ratio of the total mole number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the ethylene glycol is 1:(1.2-1.5).
[0011] Preferably, at least one of a composite catalyst, an antioxidant and an anti-ether stabilizer is added to the copolymerization synthesis system.
[0012] Preferably, the composite catalyst is a mixture of at least two of germanium oxide, antimony trioxide, aluminum trioxide, zinc acetate, titanium isopropoxide and stannous octoate.
[0013] The antioxidant is selected from one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl)phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate.
[0014] More preferably, the antioxidant is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:1, namely antioxidant B215.
[0015] Preferably, the anti-ether stabilizer is selected from one or more of phosphoric acid, trimethyl phosphate and triphenyl phosphate.
[0016] Preferably, the molar ratio of the total mole number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the composite catalyst is 1:(0.0001-0.0002).
[0017] Preferably, the molar ratio of the total mole number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the antioxidant is 1:(0.0001-0.001).
[0018] Preferably, the molar ratio of the total mole number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the anti-ether stabilizer is 1:(0.00001-0.0001).
[0019] Preferably, the composite catalyst is a mixture of germanium oxide and antimony trioxide in a molar ratio of 110:50, more preferably 110 ppm:50 ppm.
[0020] The copolymerization synthesis reaction includes pulping, esterification, polycondensation and pelletizing.
[0021] More preferably, a composite catalyst, an antioxidant and an anti-ether stabilizer are also added to the copolymerization synthesis system, and the specific order of adding is: first mix 2,5-furandicarboxylic acid with the third monomer hydroxy acid, and then add the composite catalyst, antioxidant, ethylene glycol and anti-ether stabilizer in sequence, and then perform pulping.
[0022] Preferably, the beating is carried out under closed conditions with a protective atmosphere, specifically using a reactor with a N2 atmosphere.
[0023] Preferably, the temperature of the esterification reaction is 160-195° C. and the pressure is 35-56 kPa.
[0024] Preferably, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction, wherein the pre-polycondensation reaction is carried out at 200 to 235° C. and a vacuum degree of 10 -1kPa, the function is to remove excess ethylene glycol; the final polycondensation reaction is carried out at 255-262°C and 80-200 Pa vacuum, more preferably 80 Pa, and finally a melt with a viscosity of about 0.6-0.9 dl / g is obtained.
[0025] The synthesis route of the PEF hydrogen bond enhanced modified polyester material of the present invention is as follows (taking 5-HIPA as an example):
[0026] The present invention also provides a PEF hydrogen bond enhanced modified polyester material prepared by the above preparation method.
[0027] As described above, the PEF hydrogen bond enhanced modified polyester material and the preparation method thereof of the present invention have the following beneficial effects: (1) The third monomer hydroxy acid used in the present invention is a mature commodity, economical and cheap; (2) The preparation process is simple and can be realized by simply adjusting parameters on existing mature equipment, with low cost; (3) The introduced hydroxyl groups act as hydrogen bond donors to strengthen the PEF copolyester material, thereby increasing the interaction strength between PEF chains and the chain stacking density. Only a small amount of addition can improve the toughness, melt strength, and crystallization rate of PEF, and the barrier properties of PEF copolyester remain more than 5 times that of PET. (4) Explore the influence of hydrogen bonds on the barrier properties of polyester materials and their applications, develop ways and methods for PEF modification, and guide the subsequent development of modified materials that can achieve high barrier properties with a small amount of addition; (5) With the market price of bio-based PEF raw materials at about RMB 200,000 per ton, it is conducive to economic sustainable development and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Shown are the chemical structural formulas and corresponding NMR spectra of the products obtained in Examples 1 to 6 and Comparative Example 1 (the lowercase English numbers of different peaks in the NMR spectra correspond to the chemical structures and positions of the products): A is the structural analysis of 0.5% 5-HIPA copolymerization products; B is the characteristic signal area superimposed hydrogen spectrum of the PEF hydrogen bond enhanced modified polyester material prepared with different proportions of 5-HIPA in Examples 1 to 6.
[0029] Figure 2 Shown are the Fourier transform infrared spectra of the products obtained in Examples 1 to 6 and Comparative Example 1: hydroxyl (A: 5-hydroxyisophthalic acid), oxygen-methylene-oxygen (O-CH2-CH2-O) stretching vibration (B: ethylene glycol), aromatic ring-aromatic ring-carbonyl (C: 2,5-furandicarboxylic acid) and methylene (CH) stretching vibration (D: 2,5-furandicarboxylic acid and 5-hydroxyisophthalic acid).
[0030] Figure 3 The X-ray diffraction patterns (A) of the products obtained in Examples 2 to 4 and Comparative Example 1 and the differential scanning calorimetry (DSC) isothermal crystallization curves (B) of the products obtained in Examples 1 to 6 and Comparative Example 1 at 160°C are shown.
[0031] Figure 4 The characterization of the thermal properties of the copolyester is shown: the thermal stability (A) determined by thermogravimetric analysis (TGA) as the content of 5-hydroxyisophthalic acid (5-HIPA) varies; the differential scanning calorimetry (DSC) temperature rise curve (B) of the glass transition temperature (Tg) of the products obtained in Examples 1 to 6 and Comparative Example 1 as the content of 5-HIPA varies.
[0032] Figure 5 The figure shows the transparent coating effect of the product obtained in Example 7 after being blown into a film.
[0033] Figure 6 The bending test diagram of the product obtained in Example 2 is shown: the upper diagram is before bending, and the lower diagram is after bending. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0035] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0036] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0037] Example 1 This embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: 0.5 mol% of 5-hydroxyisophthalic acid (5-HIPA: 3.6 g, 0.02 mol) and 99.5 mol% of 2,5-furandicarboxylic acid FDCA (497.5 g, 3.18 mol) were fully mixed, and then 120 ppm of germanium oxide, 40 ppm of antimony trioxide, and 500 ppm of antioxidant B215 were added and mixed evenly, wherein the antioxidant B215 was a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:1; 20 ppm of triethyl phosphate anti-ether stabilizer was dissolved in 4 mol of ethylene glycol EG; At room temperature, the above two materials were added to a 2.5L reactor and stirred for half an hour. During this period, the gas atmosphere in the reactor was replaced with inert gas three times. The temperature of the reactor was controlled at 160-195°C and the pressure was 35-56kPa for esterification reaction. After the esterification rate calculated by the water output exceeded 90%, pre-polycondensation was carried out; At 230 °C, slowly evacuate to a vacuum degree of 10 -1 kPa conditions to remove excess ethylene glycol, the reaction time is 50min; the final polycondensation reaction is carried out at a polycondensation temperature of 255-262°C and a vacuum degree of 80-200Pa, the induction period is 60min, and the polycondensation time is 27min; the stirring is stopped after the torque of the stirring paddle reaches the expected value, and a polymer melt with a viscosity of about 0.647dl / g is obtained; the polymer melt is sent to a pelletizer by pressure for cooling, pelletizing, and drying to obtain a bio-based furan polyester, which is a PEF hydrogen bond enhanced modified polyester material, denoted as PEHIF- 0.5 .
[0038] The chemical structure and H NMR spectrum of the product obtained in Example 1 are as follows Figure 1 As shown, the obtained product is a random copolymer, and the content of 5-HIPA is 0.5%, which is consistent with the feed amount. The chemical structures corresponding to the various signal peaks analyzed by nuclear magnetic resonance are marked with the same letters.
[0039] Example 2 This embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: 1 mol% of 5-hydroxyisophthalic acid (5-HIPA) (7.2 g, 0.04 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, and then 120 ppm of germanium oxide, 40 ppm of antimony trioxide, and 500 ppm of antioxidant B215 were added and mixed evenly. The antioxidant B215 was a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1; 20 ppm of triethyl phosphate anti-ether stabilizer was dissolved in 4 mol of EG; At room temperature, the above two materials were added to a 2.5L reactor and fully stirred for half an hour. During this period, the gas atmosphere in the reactor was replaced with inert gas three times. The temperature of the reactor was controlled at 160-195°C and the pressure was 35-56Kpa for esterification reaction. After the esterification rate calculated by the water output exceeded 90%, pre-polycondensation was carried out; The pre-polycondensation was carried out at 230°C and slowly vacuumed to remove excess ethylene glycol, and the reaction time was 50 minutes; the final polycondensation reaction was carried out at a polycondensation temperature of 255-262°C and vacuum, with an induction period of 60 minutes and a polycondensation time of 25 minutes; the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.671 dl / g was obtained; The polymer melt is sent to a pelletizer under pressure for cooling, pelletizing and drying to obtain bio-based furan polyester, which is a PEF hydrogen bond enhanced modified polyester material, denoted as PEHIF-1.
[0040] The bending test diagram of the product obtained in Example 2 is as follows Figure 6 As shown, the upper figure shows the state before bending, and the lower figure shows the state after bending.
[0041] Example 3 This embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: After 2 mol% of 5-hydroxyisophthalic acid (5-HIPA) (14.4 g, 0.08 mol) and 98 mol% of 2,5-furandicarboxylic acid FDCA (490 g, 3.12 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 22 min, and the stirring was stopped after the stirring paddle torque reached the expected value, and a melt with a viscosity of about 0.675 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0042] Example 4 The present embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: 3 mol% of 5-hydroxyisophthalic acid (5-HIPA) (21.6 g, 0.12 mol) and 97 mol% of 2,5-furandicarboxylic acid FDCA (485 g, 3.10 mol) are fully mixed, and the subsequent steps are the same as those in Example 2, the polycondensation time is 20 min, and the stirring is stopped after the torque of the stirring paddle reaches the expected value, and a melt with a viscosity of about 0.715 dl / g is obtained; the polymer melt is sent to a pelletizer by pressure for cooling, pelletizing, and drying; and a bio-based furan polyester is obtained, which is a PEF hydrogen bond enhanced modified polyester material, recorded as PEHIF-3.
[0043] Example 5 This embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: After 4 mol% of 5-hydroxyisophthalic acid (28.8 g, 0.16 mol) and 96 mol% of 2,5-furandicarboxylic acid FDCA (480 g, 3.07 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 20 min, and the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.658 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing, and drying to obtain a bio-based furan polyester, which is a PEF hydrogen bond enhanced modified polyester material, recorded as PEHIF-4.
[0044] Example 6 This embodiment provides a method for preparing a PEF hydrogen bond enhanced modified polyester material, comprising the following steps: After 5 mol% of 5-hydroxyisophthalic acid (5-HIPA) (36 g, 0.20 mol) and 95 mol% of 2,5-furandicarboxylic acid FDCA (480 g, 3.04 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 22 min, and the stirring was stopped after the stirring paddle torque reached the expected value, and a melt with a viscosity of about 0.799 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material, recorded as PEHIF-5.
[0045] Example 7 After 7 mol% of 5-hydroxyisophthalic acid (5-HIPA) (50.4 g, 0.28 mol) and 93 mol% of 2,5-furandicarboxylic acid FDCA (465 g, 2.97 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 20 min, and the stirring was stopped after the stirring paddle torque reached the expected value, and a melt with a viscosity of about 0.835 dl / g was obtained. The polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material, recorded as PEHIF-7.
[0046] The morphology of the product obtained in this embodiment after being blown into a film is shown in the figure Figure 5 As shown, the film thickness is 0.01 mm and the light transmittance is 94%. The material covered by the film can be clearly seen, which meets the application requirements of packaging materials and some optical films.
[0047] Example 8 After 10 mol% of 5-hydroxyisophthalic acid (5-HIPA) (72 g, 0.40 mol) and 90 mol% of 2,5-furandicarboxylic acid FDCA (450 g, 2.88 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 20 min, and the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.891 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0048] Example 9 After 1 mol% of 2,5-hydroxyterephthalic acid (0.40 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 25 min, and the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.837 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing, and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0049] Example 10 After 1 mol% of 5-hydroxyisophthalic acid dimethyl ester (0.40 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, 100 ppm of zinc acetate was additionally added as the third component of the catalyst, and the subsequent steps were the same as in Example 2, the polycondensation time was 25 min, and the stirring was stopped after the stirring paddle torque reached the expected value, and a melt with a viscosity of about 0.689 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing, and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0050] Embodiment 11 After 1 mol% of 5-carboxyvanillic acid (0.40 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 25 min, and the stirring was stopped after the stirring paddle torque reached the expected value, and a melt with a viscosity of about 0.737 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0051] Example 12 After 1 mol% of 4,5-dihydroxyisophthalic acid (0.40 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 25 min, and the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.674 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing and drying; and a bio-based furan polyester was obtained, which was a PEF hydrogen bond enhanced modified polyester material.
[0052] Example 13 After 1 mol% of 4,5,6-trihydroxyisophthalic acid (0.40 mol) and 99 mol% of 2,5-furandicarboxylic acid FDCA (495 g, 3.17 mol) were fully mixed, the subsequent steps were the same as in Example 2, the polycondensation time was 25 min, and the stirring was stopped after the torque of the stirring paddle reached the expected value, and a melt with a viscosity of about 0.653 dl / g was obtained; the polymer melt was sent to a pelletizer by pressure for cooling, pelletizing, and drying; the bio-based furan polyester was obtained, which is the PEF hydrogen bond enhanced modified polyester material Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that 5-hydroxyisophthalic acid (5-HIPA) is not added, and the steps include: 2,5-furandicarboxylic acid FDCA (500 g, 3.2 mol) and a total of 160 ppm of a composite catalyst and 500 ppm of an antioxidant are uniformly mixed; 20 ppm of an anti-ether stabilizer is dissolved in 4 mol of EG; At room temperature, the above two materials are added to a 2.5L reactor and stirred for half an hour. During this period, the gas atmosphere in the reactor is replaced three times with inert gas. The reactor temperature is controlled at 160-195°C and the pressure is 35-56Kpa for esterification reaction. After the esterification rate calculated by the water output exceeds 90%, pre-polycondensation is carried out. Pre-polycondensation is carried out at 200-235°C and slowly vacuumed to remove excess ethylene glycol. The reaction time is 50min; the final polycondensation reaction is carried out at a polycondensation temperature of 255-262°C and vacuum, with an induction period of 60min and a polycondensation time of 27min; the stirring is stopped after the torque of the stirring paddle reaches the expected value, and a melt with a viscosity of about 0.622dl / g is obtained; the polymer melt is sent to a pelletizer by pressure for cooling, pelletizing, and drying to obtain a polyester material, which is recorded as PEHIF-0.
[0053] The nuclear magnetic superposition spectra of Comparative Example 1 and Examples 1-6 are as follows Figure 1 As shown, the characteristic area representing the 5-HIPA content is magnified, and its content calculated by NMR is consistent with the feed amount.
[0054] The properties of the materials obtained in each embodiment and comparative example 1 were tested: Nuclear magnetic resonance (NMR): Proton spectra were measured on a 400 MHz NMR spectrometer (Bruker, Germany) at room temperature using deuterated trifluoroacetic acid (chemical shift δ=11.5 ppm in the proton spectrum) as solvent.
[0055] Thermogravimetric analysis (TGA): The materials were tested using a TA Q500 thermogravimetric analyzer from TA Corporation of the United States. According to the national standard GB / T 19466.6-2009, all samples were heated from 30°C to 600°C at a heating rate of 10°C per minute under a nitrogen atmosphere.
[0056] Differential Scanning Calorimetry (DSC): DSC analysis was performed using a TA-Q2000 thermal analyzer in accordance with the national standard GB / T19466.3-2004, with a heating rate of 10°C / min.
[0057] X-ray diffraction (XRD): XRD analysis was performed using an Ultima IV instrument; test angle: wide angle 5–90°, conventional test rate: 5° / min.
[0058] Melt flow index (MFI) test: using RL1100 melt flow index tester, according to the national standard GB / T 3682, tested at 260°C.
[0059] The chemical structural formula and NMR spectrum of the products obtained in Examples 1 to 6 and Comparative Example 1 are as follows Figure 1 As shown, the letters marked in the chemical structure are Figure 1The marked peaks correspond to the product structures and positions corresponding to the lowercase English numbers of the different peaks in the NMR image. Figure 1 It can be seen that when the third monomer hydroxy acid participates in the copolymerization, the hydroxyl group does not participate in the reaction. By adding different proportions of the third monomer hydroxy acid, PEF copolyester materials with different hydrogen bond content enhancements are obtained.
[0060] The Fourier transform infrared spectra of the products obtained in Examples 1 to 6 and Comparative Example 1 are as follows: Figure 2 As shown, from Figure 2 It can be seen that: hydroxyl group (A: 5-hydroxyisophthalic acid), oxygen-methylene-oxygen (O-CH2-CH2-O) stretching vibration (B: ethylene glycol), aromatic ring-aromatic ring-carbonyl group (C: 2,5-furandicarboxylic acid) and methylene (CH) stretching vibration (D: 2,5-furandicarboxylic acid and 5-hydroxyisophthalic acid).
[0061] The X-ray diffraction patterns of the products obtained in Examples 2 to 4 and Comparative Example 1 are as follows: Figure 3 As shown in A in the figure, the differential scanning calorimetry (DSC) isothermal crystallization curves of the products obtained in Examples 1 to 6 and Comparative Example 1 at 160°C are as follows Figure 3 As shown in B.
[0062] The thermal stability of the 5-hydroxyisophthalic acid (5-HIPA) solution was determined by thermogravimetric analysis (TGA). Figure 5 A in the embodiment 1 to 6 and the comparative example 1 the glass transition temperature (Tg) of the product obtained with the 5-HIPA content of the differential scanning calorimetry (DSC) temperature rise curve as shown Figure 5 As shown in B.
[0063] The results are shown in Table 1: Table 1. Component structure and performance data of the materials obtained in Examples 1 to 8 and Comparative Example 1 In Table 1, [η] is the intrinsic viscosity of the product; Xc (%) is the crystallinity; ρ s is the product density; T g is the glass transition temperature; T d is the initial decomposition temperature.
[0064] The materials obtained in Examples 1 to 8 and Comparative Example 1 were injection molded into standard specimens, and the corresponding mechanical properties were tested according to national standards. The tensile and bending performance tests were all in accordance with GB / T 1040 2006, wherein the tensile rate of the tensile performance test was 50 mm / min, and the test environment temperature was 11°C; The gas permeability test was conducted according to the national standard GB / T 1038-2022. The results are shown in Table 2: Table 2. Mechanical properties and barrier properties of materials prepared in Examples 1 to 6 and Comparative Example 1 As can be seen from Table 1 and Table 2, by comparing the elongation at break of the materials prepared in Examples 1 to 8 and Comparative Example 1, it is found that the elongation at break after the modification of the present invention is increased from about 5% (Comparative Example 1) to more than 11% (Example 2), and the toughness is significantly improved; the melt index is reduced from 94.6 g / (10 min) (Comparative Example 1) to 12.35 g / (10 min) (Example 8), and the melt strength is increased; the gas barrier performance is still maintained at PET (the oxygen permeability coefficient is about: 0.0597 ml (g) mm / m 2 ·d·MPa) (Examples 3-4), especially when the addition amount is 1% and 2%, the gas barrier property of the copolyester is improved compared with that of pure PEF. In addition, the crystallization rate increases with the increase of 5-HIPA content, which is conducive to accelerating crystallization during processing, and the thermal stability is improved, and the glass transition temperature is maintained above 80°C.
[0065] The above examples are for the purpose of illustrating the embodiments disclosed by the present invention and are not to be construed as limitations of the present invention. In addition, the various modifications listed herein and the variations of methods and compositions in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been specifically described in conjunction with various specific preferred embodiments of the present invention, it should be understood that the present invention should not be limited to these specific embodiments. In fact, various modifications obvious to those skilled in the art as described above to obtain the invention should be included within the scope of the present invention.
Claims
1. A method for preparing a PEF hydrogen bond enhanced modified polyester material, characterized in that: After 2,5-furandicarboxylic acid is blended with a third monomer hydroxy acid, they are copolymerized under the action of ethylene glycol to form a bio-based furan polyester, which is the PEF hydrogen bond reinforced modified polyester material.
2. The preparation method according to claim 1, characterized in that: The third monomeric hydroxy acid is selected from one or more of 5-hydroxyisophthalic acid, 2,5-hydroxyterephthalic acid, 5-hydroxyisophthalic acid dimethyl ester, 5-carboxyvanillic acid, 4,5-trihydroxyisophthalic acid and 4,5,6-trihydroxyisophthalic acid.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the 2,5-furandicarboxylic acid to the third monomer hydroxy acid is (90-99.5): (0.5-10).
4. The preparation method according to claim 1, characterized in that: The molar ratio of the total mole number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the ethylene glycol is 1:(1.2-1.5).
5. The preparation method according to claim 1, characterized in that: The copolymerization synthesis system further includes at least one of a composite catalyst, an antioxidant and an anti-ether stabilizer; the composite catalyst is a mixture of at least two of germanium oxide, antimony trioxide, aluminum trioxide, zinc acetate, titanium isopropoxide and stannous octoate; the antioxidant is selected from tetra[ β -(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, β One or more of octadecyl-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and dilauryl thiodipropionate; the anti-ether stabilizer is selected from one or more of phosphoric acid, trimethyl phosphate and triphenyl phosphate.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the total molar number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the composite catalyst is 1:(0.0001-0.0002); the molar ratio of the total molar number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the antioxidant is 1:(0.0001-0.001); the molar ratio of the total molar number of the 2,5-furandicarboxylic acid and the third monomer hydroxy acid to the anti-ether stabilizer is 1:(0.00001-0.0001).
7. The preparation method according to claim 6, characterized in that: The composite catalyst is a mixture of germanium oxide and antimony trioxide in a molar ratio of 110:
50.
8. The preparation method according to claim 1, characterized in that: The copolymerization synthesis reaction includes pulping, esterification, polycondensation and pelletizing.
9. The preparation method according to claim 8, characterized in that: The pulping is carried out under a closed condition with a protective atmosphere; the temperature of the esterification reaction is 160~195℃ and the pressure is 35~56kPa; the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction, and the pre-polycondensation reaction is carried out at 200~235℃ and a vacuum degree of 10 -1 kPa; the final polycondensation reaction is carried out at 255-262°C and 80-200 Pa vacuum to obtain a melt with a viscosity of about 0.6-0.9 dl / g.
10. A PEF hydrogen bond enhanced modified polyester material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method and application of bio-based furan polyester with high gas barrier property
CN120504821A
Preparation method and application of a high-gas-barrier bio-based furan polyester
CN120504821B